2006
DOI: 10.1097/01.fjc.0000211762.06271.ce
|View full text |Cite
|
Sign up to set email alerts
|

Red Wine Induced Modulation of Vascular Function: Separating the Role of Polyphenols, Ethanol, and Urates

Abstract: By using red wine (RW), dealcoholized red wine (DARW), polyphenols-stripped red wine (PSRW), ethanol-water solution (ET), and water (W), the role of wine polyphenols, ethanol, and urate on vascular function was examined in humans (n = 9 per beverage) and on isolated rat aortic rings (n = 9). Healthy males randomly consumed each beverage in a cross-over design. Plasma ethanol, catechin, and urate concentrations were measured before and 30, 60 and 120 minutes after beverage intake. Endothelial function was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…In human subjects, an improvement in endothelium-dependent vasodilatation has been reported after the acute intake of white wine or red wine with a meal by subjects with IHD (54) ; also it has been observed that an acute intake of red grape polyphenol extract, red wine or dealcoholised red wine cause an increase in flow-mediated dilatation, peaking at 60 min (54,55) . Nevertheless, in another study (53) red wine, but not polyphenols from red wine, produced an enhancement of endothelial response, despite a similar catechin concentration in both products. Intake of grape juice or grape seed extract for 2-3 weeks also caused a significant increase in flow-mediated dilatation, compared with the control group (56,57) .…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…In human subjects, an improvement in endothelium-dependent vasodilatation has been reported after the acute intake of white wine or red wine with a meal by subjects with IHD (54) ; also it has been observed that an acute intake of red grape polyphenol extract, red wine or dealcoholised red wine cause an increase in flow-mediated dilatation, peaking at 60 min (54,55) . Nevertheless, in another study (53) red wine, but not polyphenols from red wine, produced an enhancement of endothelial response, despite a similar catechin concentration in both products. Intake of grape juice or grape seed extract for 2-3 weeks also caused a significant increase in flow-mediated dilatation, compared with the control group (56,57) .…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%
“…Also, these effects on the development of atheromatous plaque were presumably due not only to their antioxidant effects, but also to inhibition of cell proliferation in smooth muscle, regulation of adhesion molecules and reduction of the flux of atherogenic molecules from the endothelium to the arterial wall (52,53) .…”
Section: Effects On Atheromatous Plaquementioning
confidence: 99%
See 2 more Smart Citations
“…3 In addition, red wine and dealcoholized red wine increase flow-mediated vasodilation of the brachial artery in healthy subjects. 4,5 Intake of red wine also counteracts endothelial dysfunction produced by high-fat diet in human volunteers, 6 and red wine increases flow-mediated vasodilation and decreases blood pressure in adult cigarette smokers.…”
Section: Article See P 1065mentioning
confidence: 99%